Harnessing the non-specific immunogenic effects of available vaccines to combat COVID-19 - Pouria Mosaddeghi; Farbod Shahabinezhad; Mohammadreza Dorvash; Mojtaba Goodarzi; Manica Negahdaripour (Taylor & Francis Group, 2021)
No proven remedy is identified for COVID-19 yet. SARS-CoV-2, the viral agent, is recognized by some endosomal and cytosolic receptors following cell entry, entailing innate and adaptive immunity stimulation, notably through interferon induction. Impairment in immunity activation in some patients, mostly elderlies, leads to high mortalities; thus, promoting immune responses may help. BCG vaccine is under investigation to prevent COVID-19 due to its non-specific effects on the immune system. However, other complementary immune-induction methods at early stages of the disease may be needed. Here, the potentially preventive immunologic effects of BCG and influenza vaccination are compared with the immune response defects caused by aging and COVID-19. BCG co-administration with interferon-α/-β, or influenza vaccine is suggested to overcome its shortcomings in interferon signaling against COVID-19. However, further studies are highly recommended to assess the outcomes of such interventions considering their probable adverse effects especially augmented innate immune responses and overproduction of proinflammatory mediators.